Streetwear as the Material Foundation of Skate Culture and Collective Identity - Oktavian Satrio Abimanyu; Sahruman Sahruman (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This article examines streetwear as the primary material catalyst in the formation of skate culture as a distinct collective identity and subculture. Drawing on Dick Hebdige's subculture theory and Daniel Miller's material culture framework, the study argues that functional clothing including flat-soled shoes, baggy pants, and graphic tees was not merely aesthetic apparel but the ideological infrastructure through which a new community of practice was constituted. Through historical and archival analysis of skate media, brand histories, and documentary records from the 1970s to the 2000s, the article demonstrates that streetwear simultaneously served as functional tool, identity marker, community boundary, and expression of shared anti-mainstream values. As skate streetwear transitioned from a localized DIY subculture into a global commodity, its original cultural codes were paradoxically both diluted and diffused into mainstream youth culture worldwide. The study contributes to broader understandings of how everyday material objects catalyze the formation of entirely new subcultures.